1973
DOI: 10.1073/pnas.70.8.2189
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Long Pyrimidine Polynucleotides in HeLa Cell Nuclear DNA: Absence of Polydeoxythymidylate

Abstract: HeLa cell nuclear DNA contains an unexpectedly large amount of long pyrimidine polynucleotides.These sequences were detected in DNA labeled with ['HI thymidine by treatment with formic acid-diphenylamine and subsequent analysis by polyacrylamide gel electrophoresis. About 0.5% of the total thymine residues were found in polynucleotides that migrated more slowly than 4S RNA. No polynucleotides of comparable size were detected in Escherichia coli DNA. The pyrimidine polynucleotides contained no pure poly(dT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1974
1974
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…RNase digestion (pancreatic RNase cuts at C and U residues, while T1 RNase cuts at G) of this mRNA preparation revealed a resistant fraction presumed to be poly(A) (Lim and Canellakis 1970;Edmonds et al 1971;Adesnik et al 1972;Mendecki et al 1972;Birnboim et al 1973). Since long poly(A) tracts were not thought to be DNA-templated (Birnboim et al 1973;Jelinek et al 1973), a poly(A) polymerase was sought and found that was subsequently shown to be responsible for poly(A) tail formation on mRNA (Winters and Edmonds 1973a,b). The function of mRNA poly(A) could only be guessed at in these initial studies.…”
Section: Polyadenylation Signals and 39 Noncoding Rna (Ncrna) Sequencesmentioning
confidence: 94%
“…RNase digestion (pancreatic RNase cuts at C and U residues, while T1 RNase cuts at G) of this mRNA preparation revealed a resistant fraction presumed to be poly(A) (Lim and Canellakis 1970;Edmonds et al 1971;Adesnik et al 1972;Mendecki et al 1972;Birnboim et al 1973). Since long poly(A) tracts were not thought to be DNA-templated (Birnboim et al 1973;Jelinek et al 1973), a poly(A) polymerase was sought and found that was subsequently shown to be responsible for poly(A) tail formation on mRNA (Winters and Edmonds 1973a,b). The function of mRNA poly(A) could only be guessed at in these initial studies.…”
Section: Polyadenylation Signals and 39 Noncoding Rna (Ncrna) Sequencesmentioning
confidence: 94%
“…Since pyrimidine nucleotides are quite stable to this treatment they appear as nucleotides and a series of pyrimidine-containing oligonucleotides (1). When HeLa (human) DNA was degraded in this way, unexpectedly long pyrimidine tracts were found, in addition to the usual products of digestion (2). Both the size and number of these tracts differed greatly from that predicted assuming a random distribution of pyrimidines.…”
mentioning
confidence: 91%
“…Ninety percent formic acid (1.5 ml) -2.7% diphenylamine was added and the mixture was incubated for 18-20 hr at 300 in a darkened, Teflon-stoppered tube. Formic acid and diphenylamine were removed by a slight modification of our previous procedure (2). One milliliter of solution containing 10 M urea, 1 M sodium acetate, and 100 lig of tRNA was added to the hydrolysis mixture and it was extracted three times with 5 ml of diethyl ether.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that these poly(A) sequences are not encoded in DNA, but are added post-transcriptionally: (a) cordycepin blocks synthesis of poly(A) and appearance of mRNA into the cytoplasm, but does not inhibit synthesis of HnRNA (5,7,8,11,12); (b) the number and size of poly(dT) sequences in mammalian nuclear DNA has been determined by isolation of polypyrimidine sequences in DNA after depurination; these poly(dT) sequences could account for only a very small fraction of the poly(A)200 sequences in mRNA (13); and (c) adenovirus type-2 mRNA contains poly(A) sequences of 100-200 bases, yet adenovirus DNA contains no poly(dT) sequences of equivalent size detectable by RNA DNA hybridization (14).…”
mentioning
confidence: 99%